Indigenous technical knowledge of farmers in dry farming - K. Thangaraja; C. Karthikeyan (Journal of Agricultural Extension Management, 2025)
Dry land agriculture in India is always a challenge, since crop production in dry land depends on the vagaries of monsoon. Dry land areas receive less than 750 mm rainfall. Out of the net sown area of 136.18m ha, the dry land accounts for 93.13 m ha (68.4%) and contributes 40 per cent of total human population, 60 per cent of cattle heads and 44 per cent to total food production in India (Kannaiyan et al., 2001). In Tamil Nadu, area under dry farming constitutes 52 per cent of the total cultivable area and contributes to 40 per cent of total food production. The productivity of crops grown .in dry land is not only low but also remains stagnant over years. Most of the areas of Tamil Nadu come under semiarid tropical climate, except the hilly regions and East coast. Out of 5.50 m ha of net sown area, nearly 3.20 m ha are rain fed (Kannaiyan et al., 2001)